Microstructural, dielectric, mechanical, and biological properties of hydroxyapatite (HAp)/BZT-BCT (0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3) bio-composites with improved mechano-electrical properties for bone repair. Issue 17 (1st September 2022) - Swain, Sujata; Bhaskar, Rakesh; Mishra, Balaram; Gupta, Mukesh Kumar; Sonia; Dasgupta, Sudip; Kumar, Pawan
Abstract: Hydroxyapatite (HAp; Ca10 (PO4 )6 (OH)2 ) is a commonly used biomaterial for bone tissue repair applications but it has poor electrical conductivity. Whereas, BZT-BCT (0.5Ba(Zr0.2 Ti0.8 )O3 -0.5(Ba0.7 Ca0.3 )TiO3 ) is a lead-free piezoelectric material which can mimic the stress-generated electric potential of electrically-excitable tissues such as bone. This study investigated the mechanical, electrical and bio properties of xHAp/(1-x)BZT-BCT composites. xHAp/(1-x)BZT-BCT composites (with x = 5, 10, 15 and 20 wt%) were synthesized by high energy ball milling (HEBM) assisted solid-state reaction route. X-ray diffraction, scanning electron microscopy, density measurements and cell-material interaction studies of sintered HAp/BZT-BCT composites were carried out and discussed in detail. Dielectric properties of sintered composites were evaluated and compared with the existing theoretical models. Different mechanical properties like Vicker's hardness, fracture toughness, and diametral tensile strength were measured to assess the usability of synthesized composites for load-bearing orthopaedic applications. These various studies showed that incorporation of BZT-BCT in HAp improved its mechanical and electrical properties and thereby significantly increased the proliferation of human osteogenic MG-63 cells. Among all the composites, better mechanical, electrical and biological properties were obtained in 10HAp/90BZT-BCT composites.